OPTIMIZATION OF “HALO POLISI” PROGRAM TO IMPROVE RRI MEDAN'S PUBLIC SERVICES AS A PUBLIC BROADCASTING INSTITUTION - Salsabillah Ritonga; Irma Yusriani Simamora (Journal Analytica Islamica, 2025)
This study aims to analyze the implementation, management strategies, and obstacles in optimizing the Halo Polisi program on RRI Medan as a medium for complaints and improving public services. The research method used is descriptive qualitative with data collection through interviews, observations, and documentation of sources directly related to the program. Strategies for improving the program include collaboration with the North Sumatra Regional Police, utilization of digital platforms, and selection of current issues for broadcast material. The main obstacle faced is sudden changes in sources, which affect the smooth running of broadcasts. The results of the study show that the Halo Polisi program has been running optimally, as indicated by consistent broadcast schedules, positive public response, and increased legal awareness among listeners.